Communications Pretesting; Pretesting Communication for Family Planning Programs; Measures of Success In a Not-for-profit Publication - James W. King; Myrna K. Daly (Journal of Applied Communications, 1983)
Reviews of "Communications Pretesting" by James T. Bertrand; Presting Communication for Family Planning Programs, by Iqbal Qureshi and D. Lawrence Kincaid; and "Measures of Success in a Not-for-profit Publication," by Willis Rivinus.